Shield muck filling body as well as preparation method and use method thereof
By adding slag powder, fly ash and other materials to the shield slag and using dihydrate gypsum and lime as an initiator, the problem of high cost of shield slag disposal and foundation pit backfill materials is solved, and low cost is achieved. Efficient filling body preparation, suitable for backfill of foundation pits and goafs in urban construction.
Patent Information
- Application Number
- CN202411276945.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
AI Technical Summary
During urban construction, the disposal of shield slag and the low-cost and low-strength backfill materials for foundation pits and goafs are difficult to meet. Traditional backfill materials are costly and have environmental and safety problems.
Using shield slag as filler, a specific proportion of slag powder, fly ash, exciter and retarder is added to form a filler with low strength and high fluidity, and its strength is increased through specific pretreatment and stirring steps. and stability, dihydrate gypsum and lime are used as excitants to improve the durability and density of the filler.
It realizes a low-cost shield slag filling body, has suitable compressive strength and fluidity, is suitable for secondary backfill of foundation pits and goafs in urban construction, and is environmentally friendly and safe in operation, reducing traditional filling materials cost of use.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid waste treatment, and in particular relates to a shield slag filling body, a preparation method and a use method thereof. Background Art
[0002] In the process of slurry shield excavation in underground tunnels of urban construction, mud is prepared by water, clay, bentonite, flocculant, etc. to form a mud film, and the shield slag such as stone, sand, mud, etc. in the tunnel is discharged in the form of mud cake or slag. Such slurry shield tunnel slag contains a lot of fine sand, fine sand, silty clay, and clay, and the volume of shield slag is huge. How to deal with such shield slag has always been a difficult problem in the process of urban construction.
[0003] Secondly, in the process of urban construction, a large number of foundation pits and goaf areas need to be backfilled for the second time. If solid waste without any strength is used for backfilling, it will bring many environmental and safety problems. At the same time, the traditional backfill material uses cement composite sand and gravel aggregate filling, which is also expensive. How to use low-cost and low-strength backfill materials for backfilling urgently needs a breakthrough. Summary of the invention
[0004] The purpose of the present invention is to provide a shield slag filling body, a preparation method and a use method thereof. The shield slag filling body has low strength and high fluidity, and meets the requirements of building materials. At the same time, the shield slag filling body uses waste slag as raw material, which saves costs and increases economic benefits. In order to achieve the above purpose, the present invention provides the following technical solutions:
[0005] A shield slag filling body, wherein the raw materials for preparing the body include, by weight, 1 part of shield slag, 0.1-0.3 parts of cementitious material, and 0.15-0.35 parts of water.
[0006] Preferably, the particle size of the shield slag is ≤2.36mm.
[0007] The cementitious material comprises, by weight percentage, 40% to 60% slag powder, 30% to 45% fly ash, 8% to 13% activator, 0.8% to 1.5% retarder, 0.02% to 0.04% methyl cellulose, and water to make up the balance to 100%.
[0008] Preferably, the slag powder is S95 slag powder.
[0009] Preferably, the particle size of the slag powder is 10-100 μm, and the density is ≥2.8 g / cm 3 , specific surface area ≥420m 2 / kg, 28d activity index ≥95%, the total mass fraction of Al2O3, SiO2 and CaO ≥75%; further preferably, the particle size of the slag powder is 10-45 μm, and the density is 2.9 g / cm 3 , specific surface area ≥450m 2 / kg, 28d activity index ≥96%, the total mass fraction of Al2O3, SiO2 and CaO ≥85%.
[0010] Furthermore, the total mass fraction of SiO2 and CaO in the slag powder is ≥65%.
[0011] In some preferred embodiments, the slag powder is purchased from the General Institute of Building Materials Science.
[0012] Preferably, the fly ash particle size is 10-100 μm, and the density is ≤2.5 g / cm 3 , specific surface area ≥400m 2 / kg, the total mass fraction of Al2O3, SiO2 and CaO is ≥75%; further preferably, the particle size of the fly ash is 10-80 μm, and the density is 2.2 g / cm 3 , specific surface area ≥480m 2 / kg, the total mass fraction of Al2O3, SiO2 and CaO ≥85%.
[0013] Furthermore, the total mass fraction of Al2O3 and SiO2 in the fly ash is ≥80%.
[0014] In some preferred embodiments, the fly ash is purchased from Henan Borun Casting Materials Co., Ltd.
[0015] Preferably, the mass ratio of fly ash to slag powder is 1:(1-1.6); further preferably, it is 1:(1.2-1.6).
[0016] In some preferred schemes, the present application selects specific slag and fly ash, and when the mass ratio of the fly ash to the slag powder is 1: (1-1.6), it can reduce the shrinkage rate while improving the compressive strength of the shield slag filling body. This is because the chain-like hydrated calcium silicate (aluminate) gel generated by the slag with high Si and Ca content and the three-dimensional network-like hydrated sodium silicate aluminate gel generated by the fly ash with high Si and Al content are interwoven to form a whole, which improves the strength of the system while reducing the shrinkage rate of the system and improving the stability of the system performance. However, the improvement of the system performance by only slag and fly ash is limited.
[0017] Preferably, the activator is dihydrate gypsum and lime; further preferably, the mass ratio of dihydrate gypsum to lime is (0.3-1):1; further preferably, it is (0.5-0.8):1.
[0018] Preferably, the purity of the dihydrate gypsum is ≥95%, and the particle size is 200-500 mesh; further preferably, the purity of the dihydrate gypsum is ≥99%, and the particle size is 325 mesh.
[0019] In some preferred embodiments, the dihydrate gypsum is purchased from Shandong Jinshengtai Chemical Co., Ltd.
[0020] Preferably, the purity of the lime is ≥90%, and the particle size is 400-1000 mesh; further preferably, the purity of the lime is ≥95%, and the particle size is 600-800 mesh.
[0021] In some preferred embodiments, the lime is purchased from Guilin Haowang New Materials Co., Ltd.
[0022] The present invention uses underground shield slag from the East Sixth Ring Road in Beijing. Due to the introduction of chemical substances such as sodium bentonite (strength), baking soda, and cellulose (alkalinity), the tunnel slag contains some alkaline substances, and the pH value of the shield slag reaches 9 to 10, which is alkaline. The raw materials used are alkaline, and it has been verified through experiments that the alkaline shield slag can directly stimulate the activity of high-temperature cold-extracted volcanic ash materials, but the degree of stimulation is insufficient if it is simply based on the alkaline source in the shield slag. The applicant creatively discovered that when specific dihydrate gypsum and lime are selected as activators, and the mass ratio of dihydrate gypsum to lime is (0.3 to 1):1, the strength and durability of the shield slag filling body can be further improved. This is because during use, the Ca(OH)2 generated by the lime reaction and the CaSO4 in the gypsum can jointly stimulate the active Al2O3, SiO2 and other raw materials to generate gelled products, forming a dense network structure. The calcium aluminate generated at the same time can also fill the gaps, further improving the strength and density of the filling body. The filling body can be used as a secondary backfill material for a large number of foundation pits and goafs in the process of high-quality urban construction. In addition, the present invention uses two weak alkaline calcium-based activators, dihydrate gypsum and lime, which are environmentally friendly and safe to operate. However, too much activator addition will lead to too fast a reaction speed during use, resulting in rapid coagulation and rapid hardening, which will lead to an uneven and loose structural system, and the strength will also decrease.
[0023] Preferably, the retarder is sodium lignosulfonate and sodium citrate; further preferably, the mass ratio of sodium lignosulfonate to sodium citrate is (1-3.5):1; further preferably, it is 1:1.
[0024] Preferably, the moisture content of the sodium lignosulfonate is ≤10%, and the lignosulfonate content is 50% to 70%; further preferably, the moisture content of the sodium lignosulfonate is 3% to 7%, and the lignosulfonate content is 55% to 65%.
[0025] In some preferred embodiments, the sodium lignosulfonate is purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd.
[0026] Preferably, the water content of the sodium citrate is 10% to 13%, and the sodium citrate content is ≥ 95%; further preferably, the water content of the sodium citrate is 12%, and the sodium citrate content is 99.9%.
[0027] In some preferred embodiments, the sodium citrate is purchased from Hebei Pengyu Biotechnology Co., Ltd.
[0028] Preferably, the mass ratio of the activator to the retarder is (8-12):1; more preferably, it is 10:1.
[0029] Preferably, the total mass of the activator and the retarder is 22% to 40% of the mass of the fly ash; more preferably, it is 15% to 30%.
[0030] In some preferred schemes, specific sodium lignosulfonate and sodium citrate are selected as retarders, and when the mass ratio of sodium lignosulfonate and sodium citrate is (1-3.5):1, it can not only enhance the strength of the system, but also prolong the fluidity of the system. The applicant unexpectedly found in many experiments that when the activator and retarder in the present application are selected, and the mass ratio of the activator and the retarder is (8-12):1, and the total mass of the activator and the retarder is 22% to 40% of the mass of the fly ash, the negative effect of the activator on the strength of the system can be alleviated, and the strength of the shield slag filling body can be ensured. The applicant speculates that this is because the retarder itself will form a network-like buffer film during the retarding process, which hinders the combination of crystal units on the crystal surface, makes the growth rate in all directions close to equilibrium, and promotes the crystal shape of the activator and the hydration reaction product (such as Ca(OH)2) to be close, thereby enhancing the activator's activating effect on the fly ash, reducing the negative effect of the activator, and steadily improving the strength of the system.
[0031] Preferably, the viscosity of the methyl cellulose (20 g / L, 20° C.) is ≥ 20 mPa.s, and the methoxy content is 25% to 35%; further preferably, the viscosity of the methyl cellulose (20 g / L, 20° C.) is ≥ 25 mPa.s, and the methoxy content is 28% to 32%.
[0032] In some preferred embodiments, the methylcellulose is purchased from Shanghai Kanglang Biotechnology Co., Ltd.
[0033] Preferably, the added amount of the shield slag does not exceed 90% of the total solid mass of the shield slag and the cementitious material.
[0034] Preferably, the water-to-solid ratio of the shield slag filling body is 0.2-0.28, wherein the water-to-solid ratio is the percentage of the mass of water to the mass of the total solids.
[0035] The applicant found that although shield slag can be used as one of the raw materials for preparing the filling body, it needs to be pre-treated and processed to the required particle size through specific sorting, crushing, coarse grinding, screening and other steps before it can be used. The applicant creatively found that when the shield slag is crushed to a particle size of ≤2.36mm after a specific pre-treatment step, and the water-solid ratio of the shield slag filling body is 0.2-0.28, it can ensure the strength of the shield slag filling body while improving the durability and stability of the shield slag. In the actual production process, crushing shield slag to a relatively low particle size not only requires a lot of energy consumption, but also the relatively low particle size is prone to agglomeration, affecting production stability. For example, when the water-solid ratio is low, the shield slag with a particle size of ≤2.36mm does not require enough water, and agglomeration will occur, which reduces the cohesion between the shield slag and the fly ash and slag particles in the cementitious material, resulting in an uneven system during subsequent use, thereby affecting the compressive strength of the shield slag filling body, and also affecting the fluidity of the slurry during use. However, a too high water-solid ratio will lead to excessive water content in the system, OH - The active oxides in slag and fly ash are difficult to be stimulated to form aluminosilicate gel in an environment with low alkali concentration, and the strength of the system will also decrease. When the water content of the system is high, slurry flow will occur during the molding process, affecting the stability of the system. In addition, the increase in the production of cementitious materials in shield slag will cause the OH in the system to - As the concentration increases, the generation of hydrated sodium aluminosilicate gel and hydrated calcium (aluminosilicate) gel in the system is increased, thereby improving the compressive strength of the shield slag filling body. However, considering the recovery rate of shield slag and the concept of national sustainable development, the amount of shield slag added should not exceed 90% of the total solid mass of shield slag and cementitious materials. The prepared shield slag filling body not only has a certain strength, but can also be used for secondary backfilling of a large number of foundation pits and goaf areas during urban construction, and has low cost and high utilization rate of shield slag.
[0036] Preferably, the initial fluidity of the shield soil filling body is ≥180cm, the expansion is ≥550cm, the fluidity after 1h is ≥120cm, and the drying shrinkage value after 90d is ≤8×10 -4 , 28d cube compressive strength ≥1.5MPa.
[0037] A second aspect of the present invention provides a method for preparing a shield slag filling body, comprising the following steps:
[0038] S1. Pretreatment of shield slag: sort, crush, coarsely grind and sieve the shield slag to obtain particles with a particle size of ≤2.36mm, which is the ground shield slag;
[0039] S2. Preparation of cementitious material: grinding and mixing slag powder, fly ash, activator, retarder and thickener in a ball mill to obtain cementitious material;
[0040] S3. Preparation of shield slag filling body: Mix the cementitious material obtained in step S2 and the ground shield slag obtained in step S1 according to weight parts, add water, place the mixture in a twin-shaft forced mixer and stir it evenly to obtain the shield slag filling body.
[0041] The specific process of sorting in step S1 is: use a pre-screener to screen out wood, large stones, compacted mud, etc. in the shield slag, and pile up and dry the remaining slag.
[0042] The specific process of crushing in step S1 is: the shield slag after drying is initially crushed into particles with a particle size range of 5 to 10 mm.
[0043] The crushing method includes but is not limited to mechanical crushing.
[0044] The specific process of the coarse grinding in step S1 is: the crushed shield slag is put into a ball mill for grinding and then sieving to obtain particles with a particle size of ≤2.36 mm.
[0045] The third aspect of the present invention provides a method for using a shield slag filling body, comprising the following steps: placing the shield slag filling body prepared by the above method in a concrete mixer truck and transporting it to the implementation site, and using a concrete pump to pour the engineering parts that need to be poured.
[0046] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0047] 1. The present invention provides a shield slag filling body, which uses shield slag as the main waste material, has low production cost and is easy to promote. It not only saves the cost of traditional filling materials, but also brings economic benefits to enterprises through the reuse of waste. Compared with the existing technology, the filling material prepared by this method is simple in process operation, easy to implement and easy to promote.
[0048] 2. The present invention selects slag with high Si and Ca content and fly ash with high Si and Al content, and when the mass ratio of fly ash to slag powder is 1: (1-1.6), it can improve the compressive strength of the shield slag filling body while reducing its shrinkage rate.
[0049] 3. The present invention uses specific dihydrate gypsum and lime as activators, and when the mass ratio of dihydrate gypsum to lime is (0.3-1):1, the strength and durability of the shield slag filling body can be further improved, and the invention is environmentally friendly and safe to operate.
[0050] 4. The present invention selects specific sodium lignosulfonate and sodium citrate as retarders, and when the mass ratio of the sodium lignosulfonate and sodium citrate is (1-3.5):1, it can not only enhance the strength of the system, but also prolong the fluidity of the system. At the same time, when the mass ratio of the activator and the retarder is (8-12):1, and the total mass of the activator and the retarder is 22% to 40% of the mass of the fly ash, the negative effect of the activator on the strength of the system can be alleviated, and the strength of the shield slag filling body can be ensured.
[0051] 5. The present invention crushes the shield slag into particles of
[0052] ≤2.36mm, and the water-solid ratio of the shield slag filling body is controlled to be 0.2~0.28, which can ensure the strength of the shield slag filling body while improving the durability and stability of the shield slag.
[0053] 6. In the present invention, the amount of shield slag added should not exceed 90% of the total solid mass of shield slag and cementitious materials. The prepared shield slag filling body not only has a certain strength and can be used for secondary backfilling of a large number of foundation pits and goaf areas during urban construction, but also has low cost and high utilization rate of shield slag.
[0054] 7. The shield slag filling body prepared by the present invention has an initial fluidity of ≥180cm, an expansion of ≥550cm, a fluidity of ≥120cm after 1h, and a drying shrinkage of ≤8×10 -4 ,
[0055] 28d cube compressive strength ≥1.5MPa. DETAILED DESCRIPTION
[0056] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] The raw materials used in the present invention are all commercially available, specifically:
[0058] Slag powder, particle size 10-45 μm, density 2.9 g / cm 3 , specific surface area ≥450m 2 / kg, 28d activity index ≥96%, Al2O3 accounts for 16.2%, SiO2 accounts for 31.9%, CaO accounts for 38.4%, MgO accounts for 7.0%, and the density is 2.9g / cm 3 , purchased from the General Institute of Building Materials Science.
[0059] Fly ash, particle size 10-80 μm, density 2.2 g / cm 3 , specific surface area ≥480m 2 / kg, Al2O3 accounted for 33.2%, SiO2 accounted for 50.2%, CaO accounted for 4.6%, and fly ash was purchased from Henan Borun Casting Materials Co., Ltd.
[0060] Dihydrate gypsum, purity ≥99%, particle size 325 mesh, was purchased from Shandong Jinshengtai Chemical Co., Ltd.
[0061] Lime, purity ≥95%, particle size 600-800 mesh, purchased from Guilin Haowang New Materials Co., Ltd.
[0062] Sodium lignosulfonate, with a moisture content of 3% to 7% and a lignosulfonate content of 55% to 65%, was purchased from Shanghai Hongzhuang Chemical Technology Co., Ltd.
[0063] Sodium citrate, with a moisture content of 12% and a sodium citrate content of 99.9%, was purchased from Hebei Pengyu Biotechnology Co., Ltd.
[0064] Methyl cellulose, viscosity (20 g / L, 20° C.) ≥ 25 mPa.s, methoxy content of 28% to 32%, purchased from Shanghai Kanglang Biotechnology Co., Ltd.
[0065] Cement, 42.5 cement, commercially available.
[0066] Example 1
[0067] This embodiment provides a shield slag filling body, the proportion of each component (kg / m 3 ) is: shield debris: 1517, cementitious material 252, water: 479.
[0068] The particle size of the shield slag is ≤2.36mm.
[0069] The cementitious material is prepared from the following raw materials by weight percentage: 50% slag powder, 35% fly ash, 4% dihydrate gypsum, 6% lime, 0.5% sodium wood sulfonate, 0.5% sodium citrate, 0.02% methyl cellulose, and water to make up the balance to 100%.
[0070] The method for preparing the shield slag filling body comprises the following steps:
[0071] S1. Pretreatment of shield slag: Use a pre-screener to screen out wood, large stones, compacted mud, etc. in the shield slag, collect and transport the remaining shield slag waste to a solidification pool for solidification for more than 24 hours until it solidifies and hardens into a block solidification, and then dry it. The dried shield slag is initially mechanically crushed, and then ground into particles with a grinder to a particle size of ≤2.36mm, which is the ground shield slag;
[0072] S2. Preparation of gelling material: grinding and mixing the raw materials of gelling material in a ball mill to obtain gelling material;
[0073] S3. Preparation of shield slag filling body: the cementitious material obtained in step S2 and the ground shield slag obtained in step S1 are mixed according to the proportion, and water is added, and the mixture is placed in a twin-shaft forced mixer and stirred evenly to obtain the shield slag filling body.
[0074] Example 2
[0075] The difference between this embodiment and embodiment 1 is that the raw materials for preparing the cementitious material are, by weight percentage, 45% slag powder, 35% fly ash, 4% dihydrate gypsum, 8% lime, 1% sodium wood sulfonate, 0.5% sodium citrate, 0.03% methyl cellulose, and the balance is supplemented with water to 100%.
[0076] Example 3
[0077] The difference between this embodiment and embodiment 1 is that the proportion of each component (kg / m 3 ) is: shield debris: 1561, cementitious material 195, water: 479.
[0078] Comparative Example 1
[0079] In this comparative example, cement is used to replace the cementitious material, and the proportion of each component (kg / m 3 ) is: shield debris: 1517, cement: 252, water reducing agent: 5, water: 420.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 1 is that the shield slag filling body has a ratio of each component (kg / m 3 ) is: shield debris: 1561, cementitious material 195, water: 502.
[0082] Comparative Example 3
[0083] The difference between this comparative example and Example 1 is that the raw materials for preparing the cementitious material are, by weight percentage, 50% slag powder, 20% fly ash, 4% dihydrate gypsum, 6% lime, 0.5% sodium lignosulfonate, 0.5% sodium citrate, 0.02% methyl cellulose, and the balance is supplemented with water to 100%.
[0084] Comparative Example 4
[0085] The difference between this comparative example and Example 1 is that the proportion of each component (kg / m 3 ) are: shield debris: 2548, cementitious material 252, water: 479.
[0086] Comparative Example 5
[0087] The difference between this comparative example and Example 1 is that the raw materials for preparing the cementitious material are, by weight percentage, 50% slag powder, 35% fly ash, 6% lime, 1% sodium lignosulfonate, 0.02% methyl cellulose, and water to make up the balance to 100%.
[0088] Performance Testing
[0089] The 90-day drying shrinkage test of shield slag was carried out in accordance with JC / T 603-2004 "Cement Mortar Drying Shrinkage Test"; the fluidity and expansion tests were carried out in accordance with GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials"; the 7-day and 28-day compressive strength tests were carried out in accordance with GB / T 17671-2021 "Cement Mortar Strength Test Method (ISO Method)". The results are shown in Table 1.
[0090] Table 1 Measurement results
[0091]
[0092] According to statistics, the shield slag filling body prepared in Examples 1 to 3 of the present invention has an initial fluidity of ≥180 cm, an expansion of ≥550 cm, a fluidity of ≥120 cm after 1 h, and a drying shrinkage of ≤8×10 -4 , 28d cube compressive strength ≥1.5MPa. Comparative Example 1 uses cement to prepare the filling material, which has a relatively high cost. Although the strength is high, the fluidity loss in 1h is large, reaching 70cm. Comparative Example 2 has a high water-solid ratio, Comparative Example 3 has too little fly ash addition, Comparative Example 4 has too much shield slag addition, and Comparative Example 5 does not add sodium citrate and dihydrate gypsum. The prepared shield slag does not fully meet the requirements. Therefore, the shield slag filling body prepared by the raw materials and methods described in this application has good performance and can be used for secondary backfilling of a large number of foundation pits and goafs in the process of urban construction, and has low cost and high utilization rate of shield slag.
[0093] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A shield slag filling body, It is characterized in that The raw materials for preparing the cementitious material include, by weight: 1 part of shield slag, 0.1-0.3 parts of cementitious material, and 0.15-0.35 parts of water; the raw materials for preparing the cementitious material include, by weight percentage: 40%-60% of slag powder, 30%-45% of fly ash, 8%-13% of activator, 0.8%-1.5% of retarder, 0.02-0.04% of methyl cellulose, and the balance of water is supplemented to 100%; the fly ash The mass ratio of the activator to slag powder is 1: (1-1.6); the activator is dihydrate gypsum and lime; the mass ratio of the dihydrate gypsum and lime is (0.3-1): 1; the retarder is sodium wood sulfonate and sodium citrate; the mass ratio of the sodium wood sulfonate and sodium citrate is (1-3.5): 1; the mass ratio of the activator to the retarder is (8-12): 1; the water-solid ratio of the shield slag filling body is 0.2-0.
28.
2. The shield slag filling body according to claim 1, It is characterized in that The particle size of the slag powder is 10-100 μm, and the density is ≥2.8 g / cm 3 , specific surface area ≥420m 2 / kg, 28d activity index ≥95%, Al 2 O 3 、SiO 2 The total mass fraction of CaO is ≥75%.
3. The shield slag filling body according to claim 2, It is characterized in that The SiO in the slag powder 2 The total mass fraction of CaO is ≥65%.
4. The shield slag filling body according to claim 1, It is characterized in that The particle size of the fly ash is 10-100 μm, and the density is ≤2.5 g / cm 3 , specific surface area ≥400m 2 / kg,Al 2 O 3 、SiO 2 The total mass fraction of CaO is ≥75%.
5. The shield slag filling body according to claim 4, It is characterized in that The Al in fly ash 2 O 3 and SiO 2 The total mass fraction is ≥80%.
6. The shield slag filling body according to claim 1, It is characterized in that The purity of the dihydrate gypsum is ≥95%, and the particle size is 200-500 meshes.
7. The shield slag filling body according to claim 1, It is characterized in that The added amount of the shield slag shall not exceed 90% of the total solid mass of the shield slag and the cementitious material.
8. The shield slag filling body according to any one of claims 1 to 7, It is characterized in that The initial fluidity of the shield soil filling body is ≥180cm, the expansion is ≥550cm, the fluidity after 1h is ≥120cm, and the drying shrinkage value after 90d is ≤8×10 -4 , 28d cube compressive strength ≥1.5MPa.
9. A method for preparing a shield slag filling body according to any one of claims 1 to 8, It is characterized in that The following steps are involved: S1. Pretreatment of shield slag: sort, crush, coarsely grind and sieve the shield slag to obtain particles with a particle size of ≤2.36mm, which is the ground shield slag; S2. Preparation of cementitious material: grinding and mixing slag powder, fly ash, activator, retarder and thickener in a ball mill to obtain cementitious material; S3. Preparation of shield slag filling body: Mix the cementitious material obtained in step S2 and the ground shield slag obtained in step S1 according to weight parts, add water, place the mixture in a twin-shaft forced mixer and stir it evenly to obtain the shield slag filling body.
10. A method for using the shield slag filling body according to any one of claims 1 to 8, It is characterized in that The method comprises the following steps: placing the shield slag filling body prepared by the above method in a concrete mixer truck and transporting it to the implementation site, and using a concrete pump to pour the engineering parts that need to be poured.
Citation Information
Cited By
Method for preparing controllable low-strength material from lithium slag and shield muck
CN121159213A
Cementing material based on large-dosage shield muck as well as preparation method and application of cementing material
CN121517148A
